Metacognitive Strategy in Significant Learning Using Illustrated Stories (Docentes 2.0 Journal, 2020)
Given the current social demands, the challenges in education require a human approach in turn to have cutting-edge content, in this context, the teacher must develop and implement various dynamic strategies aimed at stimulating cognitive, affective and psychological processes in The student, therefore, the teaching of metacognitive strategies emerges as an integration of practices aimed at promoting self-regulated and meaningful learning, the present work proposed as an objective to propose a metacognitive strategy aimed at promoting meaningful learning in Higher Education students from the elaboration of Illustrated Tales. To comply with the proposed objective, a qualitative and quantitative methodology was proposed focused on knowing metacognitive processes used by a group made up of 25 higher education students who prepared an illustrated story in which they reflected theoretical concepts and methodologies used in the analysis of facilities. industrial electricals. The elaboration of illustrated stories reveals metacognitive skills used by students when translating them into stories through arguments and graphic elements, this resource is not opposed to formal and deep work since it is based on previously known and studied concepts. The purpose of the proposed strategy affects the teaching-learning process, promoting the development and execution of various mental structures that activate previous knowledge that is complemented with new information under study.
Keywords: Meaningful learning, story, strategy, metacognitive process.